Orthopaedic Injuries After Introduction of Electric Scooters to Denver, Colorado. Issue 18 (15th September 2022) - McNulty, Mia; Look, Nicole; Strage, Katya; Lauder, Alexander
Abstract : Introduction: Cost and efficiency have made electric scooters (e-scooters) popular in urban areas, but many orthopaedic injuries are associated with their use. Methods: A retrospective review of e-scooter–related injuries at a level one trauma center identified injury patterns and hospital-associated costs before and after widespread commercial introduction of e-scooters. Results: Twenty-three and 197 patients were included in preimplementation and postimplementation groups, respectively. Hospital admission increased from 11% to 62% after commercial introduction. Cost of care increased from $1.8 million to $7.6 million, and 61% of orthopaedic injuries required surgery. The most common orthopaedic injuries were distal radius fractures. Seventy-three percent of the patients tested were intoxicated at the time of injury. Discussion: This study categorizes injury patterns and highlights increased hospital-related admissions and surgeries associated with e-scooters. The high rate of intoxicated rider injuries emphasizes the need for laws guiding operation of e-scooters.